FTA Method: Analyzing Factors That Influence the Development of OAP SMEs - Wahyudien, Mohammad Arief Nur; Ahistasari, Asih; Kayatun, Siti Nur; Rachmadhani, Mirga Maulana (Universitas Muhammadiyah Yogyakarta, 2024)
The poverty level in Southwest Papua, especially in the city and district of Sorong, is much higher than other areas in Southwest Papua, so small and medium enterprises (SMEs) owned by indigenous Papuans play an essential role as economic drivers. The urgency of this research is to develop indigenous Papuan businesses, which have been challenging to grow, so they must know what factors are needed to create. Several factors influence business development: capital, skills and knowledge, market access, and government support. To compete with developing Orang Asli Papua (OAP) businesses, they will be able to compete with non-OAP businesses and overcome poverty in Southwest Papua Province. This research uses the Fault Tree Analysis method to analyze the factors that influence the development of OAP SMEs. The research results show that six priorities are the main factors for developing SMEs: Education and Training, Networks and Connections, Capital Assistance, Marketing Skills, infrastructure and the role of government.